2018
DOI: 10.1021/acs.biomac.8b00784
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Molecular Weight and Functionality on Acrylated Poly(caprolactone) for Stereolithography and Biomedical Applications

Abstract: Degradable polymers are integral components in many biomedical polymer applications. The ability of these materials to decompose in situ has become a critical component for tissue engineering, allowing scaffolds to guide cell and tissue growth while facilitating gradual regeneration of native tissue. The objective of this work is to understand the role of prepolymer molecular weight and functionality of photocurable poly(caprolactone) (PCL) in determining reaction kinetics, mechanical properties, polymer degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 41 publications
1
57
0
Order By: Relevance
“…The functionality and subsequent degree of cross-linking has a more significant effect on biodegradation. Up to 2.5 times slower degradation has been observed for highly cross-linked PCL compared to loosely cross-linked structures [84]. Similarly, the polymer ratio PLA/PCL was found to affect biodegradation rates [87].…”
Section: Biocompatibility and Biodegradabilitymentioning
confidence: 94%
See 2 more Smart Citations
“…The functionality and subsequent degree of cross-linking has a more significant effect on biodegradation. Up to 2.5 times slower degradation has been observed for highly cross-linked PCL compared to loosely cross-linked structures [84]. Similarly, the polymer ratio PLA/PCL was found to affect biodegradation rates [87].…”
Section: Biocompatibility and Biodegradabilitymentioning
confidence: 94%
“…FDM fabricated feature sizes of~160 µm were reported [79], while bioprinted PCL structures with feature sizes of~200 µm were produced highlighting how process parameters can affect the morphology of the extruded PCL [80,81,83]. Concerning light-assisted fabrication, PCL structures with resolution down to 50 µm via DLP has been achieved [84]. TPP was used to decrease the feature size even further, down to 1 µm for 3D structures [85].…”
Section: Polycaprolactone (Pcl)mentioning
confidence: 99%
See 1 more Smart Citation
“…To allow photopolymerization, PCL has been modified with acrylates, 36–40 methacrylates, 41,42 and fumarates 43 . But only few studies have reported the use of photocrosslinkable PCL in SLA 36,42 …”
Section: Am Technologiesmentioning
confidence: 99%
“…The observations in recent reports have demonstrated that photoreceptor precursor cells directly isolated from developing mouse retina and transplanted into diseased hosts results in extensive donor cell death with transfer of donor cell material to remaining host photoreceptor cells, further suggesting that stem cell‐derived progeny are fragile and will be more successfully transplanted on a prefabricated biomimetic graft rather than as a cellular slurry. By dissociating cells during early retinal differentiation and seeding them onto a cell delivery scaffold where they will be allowed to mature and adhere prior to transplantation, one can mitigate acute cellular dissociation effects and maximize post‐transplant cell viability. Moreover, although retinal graft transplantation is our ultimate goal, early stage clinical trials designed to evaluate both safety and efficacy of intravitreal and subretinal injection of a suspension of human RPCs in patients are currently underway (https://clinicaltrials.gov/ numbers NCT02464436 and NCT03073733).…”
Section: Introductionmentioning
confidence: 99%